(untitled) (Eastern Journal of Medical Sciences, 2017)
Acute pancreatitis is inflammation of pancreas associated with injury to the pancreatic exocrine parenchyma. The most common causes of acute pancreatitis are obstruction of the pancreatic duct (gall stones) and alcohol. Viral infections are also well recognized etiology for pancreatitis. Here, we report a case of 16-year-old girl with acute pancreatitis caused by hepatitis A virus. The identification of this unusual complication of hepatitis A is important. Acute pancreatitis complicating fulminant viral hepatitis has been well known; however, acute pancreatitis occurring in nonfulminant hepatitis is very rare.